Modelagem e avaliação de desempenho da integração temporal no transporte público de ônibus usando grafo multiaspecto - Borges, Júlio César Nardelli (2025)
Public transportation monitoring systems generate real-time vehicle location data, which is essential for optimizing operations and creating new services. While physical integration at terminals is standard, temporal integration emerges as a valuable alternative, allowing users to change buses at no additional cost within a pre-defined period after initial boarding. This thesis proposes a multi-aspect graph (MAG) to represent and evaluate temporal integration in public bus transport. The research offers four main contributions: (1) an algorithm for itinerary detection capable of handling incomplete and inconsistent GPS data; (2) a MAG-based representation of temporal integration, modeling interactions between lines, stops, and schedules; (3) the concept of a virtual terminal, which identifies strategic transfer points outside traditional physical terminals; and (4) the use of network metrics (degree, closeness, and betweenness centralities, coverage time, temporal centrality) to quantitatively assess the impact of temporal integration. The methodology’s application to the Curitiba network demonstrated a reduction in distances traveled and neighborhood coverage times, without a significant increase in transfers. Similar results were observed in the analysis of the Belo Horizonte network, reinforcing the generality of the proposed approach. These analyses indicate the importance of virtual terminals, which can complement existing physical terminals. This research provides a valuable methodological framework for planning and managing more efficient and sustainable public transport systems.